Early infantile form of Krabbe disease: a case report - Reddy, K. Venkataramana; Soren, Chapay; Geethika, M.; Dharani, N.; Reddy, K. Sruthi (International Journal of Contemporary Pediatrics, 2021)
A 7-month-old female child, born to 2nd degree consanguineous marriage brought with complaints of gross developmental delay. Her examination revealed spasticity in all 4 limbs with brisk deep tendon reflexes with intact primitive reflexes and exaggerated startle reflex. Her MRI brain showed demyelination signs in bilateral thalami, dentate hila, and thickened optic chaisma. Age of presentation, clinico-radiological findings were suggestive of early infantile form of Krabbe disease.